Oxidative stress and gut-derived lipopolysaccharides in children affected by paediatric autoimmune neuropsychiatric disorders associated with streptococcal infections - Lorenzo Loffredo; Alberto Spalice; Francesca Salvatori; Giovanna De Castro; Cristiana Alessia Guido; Anna Maria Zicari; Paolo Ciacci; Simona Battaglia; Giulia Brindisi; Evaristo Ettorre; Cristina Nocella; Guglielmo Salvatori; et al. (BMC, 2020)
Abstract Background Paediatric autoimmune neuropsychiatric disorders associated with streptococcal infections syndrome (PANDAS) identifies patients with acute onset of obsessive-compulsive and tic disorders. The objective of this study was to evaluate serum NOX2 levels, as well as 8-iso-prostaglandin F2α (8-iso-PGF2α) and lipopolysaccharide (LPS) of PANDAS patients. Methods In this study we wanted to compare serum levels of soluble NOX2-dp (sNOX-2-dp), iso-PGF2α and LPS in 60 consecutive subjects, including 30 children affected by PANDAS and 30 controls (CT) matched for age and gender. Serum zonulin was used as intestinal permeability assay. Results Compared with CT, PANDAS children had increased serum levels of sNOX-2-dp, 8-iso-PGF2α and LPS. Bivariate analysis showed that serum sNOX2-dp was significantly correlated with LPS (Rs = 0.359; p = 0.005), zonulin (Rs = 0.444; p < 0.001) and 8-iso-PGF2α (Rs = 0.704; p < 0.001). Serum LPS significantly correlated with zonulin (Rs = 0.610; p < 0.001), and 8-iso-PGF2α (Rs = 0.591; p = 0.001). Finally, a multiple linear regression analysis showed that serum 8-iso-PGF2α and zonulin were the only independent variables associated with sNOX2-dp (R2 = 68%). Conclusion This study shows that children affected by PANDAS have high circulating levels of sNOX2-dp, isoprostanes and of LPS that could be involved in the process of neuroinflammation.